To honour and to inspire: profiles of outstanding taxonomists - Zhang, Zhi-Qiang (Zootaxa, 2011)
In this issue of Zootaxa, we open a new section to feature our outstanding taxonomists who have made great contributions to the field. These profiles are for living taxonomists who are still active, with preference for those who are authors and/or editors of Zootaxa. Most profiles will be by invitation, although we also welcome proposals and suggestions from the general readership. We are primarily interested in honouring distinguished members of our science who are the doyens of their areas of expertise (especially those in their 70s or more). As Zootaxa is mainly a journal of descriptive taxonomy, we are particularly interested in profiling taxonomists who had discovered and authored a very significant number of new taxa (e.g. 500 or more, but this number can be lowered for authors who work on some groups such as vertebrates).  In addition to stories of their life (preferably with photos), we appreciate a list of taxa that they authored, complete with a list of bibliography. We are also keen to honour great mentors who are inspirational to students and colleagues. It is our hope that the passion, dedication and contributions of our outstanding taxonomists will inspire a new generation into exploring, classifying and describing the fascinating biodiversity that surrounds us.